2015
DOI: 10.20884/1.jm.2015.10.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Pemurnian Asap Cair Dari Kulit Durian Dengan Menggunakan Arang Aktif

Abstract: ABSTRAKLimbah kulit durian dapat diolah menghasilkan asap cair dan karbon aktif dengan metode pirolisis. Untuk menghasilkan asap cair yang dapat digunakan sebagai pengawet makanan, asap cair perlu di proses dengan metode pemurnian seperti destilasi, pemurnian dengan zeolit aktif dan arang aktif. Hasil karakterisasi asap cair dari kulit durian hasil pirolisis, destilasi, pemurnian dengan zeolit aktif dan pemurnian dengan arang aktif diperoleh nilai pH berturut-turut 4,09; 3,24; 3,46; dan 2,09. Kadar asam asetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
0
2
0
3
Order By: Relevance
“…The formation of organic acids from cellulose and hemicellulose components affected the organoleptic quality of liquid smoke and served as natural preservatives (Budaraga et al, 2016). The total acid and pH were inversely proportional, with the higher concentration of acid in liquid smoke leading to a lower pH value (Rinaldi et al, 2015). The analysis of the acid content in liquid smoke derived from the pyrolysis and distillation at 100±2 °C showed that the former had a higher total acid value.…”
Section: Total Organic Acidmentioning
confidence: 99%
“…The formation of organic acids from cellulose and hemicellulose components affected the organoleptic quality of liquid smoke and served as natural preservatives (Budaraga et al, 2016). The total acid and pH were inversely proportional, with the higher concentration of acid in liquid smoke leading to a lower pH value (Rinaldi et al, 2015). The analysis of the acid content in liquid smoke derived from the pyrolysis and distillation at 100±2 °C showed that the former had a higher total acid value.…”
Section: Total Organic Acidmentioning
confidence: 99%
“…Arang aktif yang telah diaktivasi dapat mengurangi bau dan warna asap cair sebesar 20% [3]. Arang aktif bertujuan untuk mendapatkan filtrat asap cair dengan bau asap yang ringan dan tidak menyengat [4].…”
Section: Indonesiaunclassified
“…Beberapa berbahan jagung [5][6][7] dan beberapa menggunakan sawit [8]. Selanjutnya menggunakan bahan durian [9].…”
Section: Pendahuluanunclassified